Recent Progress in UV Spectroscopic and Chromatographic Methods for the Determination of Budesonide in Bulk and Formulations: Review Article (Journal of Pharma Insights and Research, 2025)
Budesonide, a potent synthetic corticosteroid with good topical efficacy and limited systemic bioavailability, has established its therapeutic potential in managing asthma, inflammatory bowel disease, and allergic rhinitis. The pharmaceutical analysis of budesonide requires precise, accurate, and validated analytical methods for quality control and research applications. UV spectrophotometry emerges as a prominent analytical technique for budesonide quantification, offering advantages of simplicity, cost-effectiveness, and reliability. The absorption maximum of budesonide at 246 nm provides a suitable wavelength for analysis, with a linearity in the concentration range of 1.4-25 µg/mL. Validation parameters including accuracy, precision, and specificity confirm the method's robustness, with recovery rates of 99-100% and minimal standard deviation. Chromatographic methods, particularly RP-HPLC, complement spectrophotometric analysis by offering enhanced selectivity and sensitivity. Notable developments include stability-indicating methods capable of separating degradation products and specialized techniques for analyzing complex formulations. Recent innovations focus on green analytical approaches and advanced applications in novel drug delivery systems, such as layer-by-layer polymeric nanoparticles. The analytical methodologies show significant potential in quality control laboratories and research settings, supporting both routine analysis and specialized pharmaceutical development applications.